Novel device for in situ process characterization of oxide/oxide ceramic matrix composites fabricated by flexible injection. Issue 5 (16th October 2018) - Scola, Alessandro; Podgorski, Michaël; Eberling‐Fux, Nicolas; Turenne, Sylvain; Ruiz, Edu
Abstract: In this work, a new manufacturing process of CMC by liquid molding was studied. An instrumented device has been developed to characterize the through‐thickness impregnation of ceramic fibers by a slurry charged with submicron ceramic particles. This instrument was used to characterize the permeability of the fibrous reinforcement and the formation of the ceramic cake by filtration of a ceramic particle suspension. Slurries containing different concentrations (10, 25, 33, and 40 vol%) of mono‐dispersed alumina particles were filtered under different pressure conditions (345, 415, 485 kPa) to optimize the cake formation and filling of fibrous reinforcements while controlling the porosity level. Ceramic cakes exhibited an average permeability of 1.0 × 10 −17  m 2 while the manufactured all‐oxide composites resulted in a permeability of 0.6 × 10 −17 m 2 . Furthermore, a mathematical model based on Darcy's law was developed in this study to predict the rate of filtering and cake formation during injection using the permeability and filtration data measured with the experimental device. This mathematical model allows to determine the filtration time to produce a dense ceramic composite with an accuracy of ±15%, which corresponds to an error of less than 0.1 mm on the thickness of formed CMC.